Are bad health and pain making us grumpy? An empirical evaluation of reporting heterogeneity in rating health system responsiveness - Gianluca Fiorentini; Giovanni Ragazzi; Silvana Robone (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
This paper considers the influence of patients' characteristics on their evaluation of a health system's responsiveness, that is, a system's ability to respond to the legitimate expectations of potential users regarding non-health enhancing aspects of care (Valentine et al. 2003a). Since responsiveness is evaluated by patients on a categorical scale, their selfevaluation can be affected by the phenomenon of reporting heterogeneity (Rice et al. 2012). A few studies have investigated how standard socio-demographic characteristics influence the reporting style of health care users with regard to the question of the health system's responsiveness (Sirven et al. 2012, Rice et al. 2012). However, we are not aware of any studies that focus explicitly on the influence that both the patients' state of health and their experiencing of pain have on the way in which they report on system responsiveness. This paper tries to bridge this gap by using data regarding a sample of patients hospitalized in four Local Health Authorities (LHA) in Italy's Emilia-Romagna region between 2010 and 2012. These patients have evaluated 27 different aspects of the quality of care, concerning five domains of responsiveness (communication, social support, privacy, dignity and quality of facilities). Data have been stratified into five sub-samples, according to these domains. We estimate a generalized ordered probit model (Terza, 1985), an extension of the standard ordered probit model which permits the reporting behaviour of respondents to be modelled as a function of certain respondents' characteristics, which in our analysis are represented by the variables "state of health" and "pain". Our results suggest that unhealthier patients are more likely to report a lower level of responsiveness, all other things being equal, while patients experiencing pain are more likely to make use of the extreme categories of responsiveness, that is, to choose the category "completely dissatisfied" or the category "completely satisfied". These results hold across all five domains of responsiveness.
Keywords: I1; I11; I19; C50; C25; 330